Correlation Between Different Physical and Engineering Properties of Tropical Peat Soils from Sarawak - Siti Noor Linda, Binti Taib; Kolay, Prabir K; Mohd Rahman, Aminur; Mohd Zain, M. I. S. (2010)
The present paper describes the physical and engineering properties of tropical peat soils from Sarawak, Malaysia. Different physical properties such as organic content (OC), liquid limit (LL), fibre content (FC), specific gravity (Gs) and engineering properties (mainly the standard Proctor test) have been conducted on remoulded peat soil samples. The results show that, the value of LL, FC, Optimum Moisture Content (OMC) increases with an increase in OC. Also the results show that, Gs and MDD decrease with increasing values of OC. Furthermore, the plot of OC against Gs from the current study is compared with other researchers; whereby the correlation shows that R2 values ranges from 0.71 to 0.95. This demonstrates that findings on local peat soils from Sarawak are in good agreement with other researchers as similar trends are observed. Consequently, geotechnical engineers can refer these correlations to comprehend the preliminary behavior of peat soil, where the geotechnical data are not readily available.